An Original Vibrodiagnostic Device to Control Linear Rolling Conveyor Reliability - Radka Jírová; Lubomír Pešík; Robert Grega (Journal of Marine Science and Engineering, 2022)
On the basis of an analysis of the number of goods that are transported and handled in maritime transport, the ports for cargo ships may be considered as places with concentrated emissions. Reducing the emissions in ports can be achieved by shortening the stay times of cargo ships. The time that ships spend in ports may be reduced to the time that is required for the effective handling of the goods. One of the solutions for effective handling is using equipment with linear rolling systems. To prevent the idle time of cargo ships and the unnecessary increment of emissions in ports because of the possible failure of the linear rolling systems, their reliability and failure prediction are greatly required. Unfortunately, the common diagnostic systems of linear rolling systems in transportation practice still fail in particular cases of great external loads. Therefore, an original solution of the diagnostic system was designed on the basis of a load-free diagnostic part with a vibration sensor that is integrated into a carriage of the linear rolling system. A functional sample of the diagnostics was produced, and the vibrations that were measured on a loaded carriage and on the diagnostic part were compared in laboratory conditions under significant external loads. Encouraging results were reached by a time-domain analysis of the measured data. On the diagnostic part, the damage appeared clearly, while, on the loaded carriage, there were no observable signs of damage.